Exploring Psychological Factors In Sports Participation Residential And Non Residential: A Comparative Analysis Of Denial - M.X. Aljinroy; M. Rajashekaran (Journal for ReAttach Therapy and Developmental Diversities, 2023)
This study investigates the influence of residential status and gender on denial and personal acceptance among sports participants. Denial, involving the avoidance of distressing emotions, and personal acceptance, reflecting the ability to acknowledge and embrace experiences, are critical aspects of athletes' psychological resilience. Understanding how residential status and gender intersect to affect these psychological constructs can inform targeted interventions to support athletes' mental health and performance. A sample of 1600 sports participants, comprising equal numbers of residential and non-residential athletes, was assessed for denial and personal acceptance levels. Results indicated significant differences based on residential status and gender, with residential athletes and men exhibiting higher denial levels, while women showed higher personal acceptance levels. These findings underscore the importance of tailored interventions to address athletes' unique psychological needs based on their residential status and gender. Further research is needed to explore additional factors contributing to athletes' psychological well-being and resilience in sports environments.